Phenomena (submission delays) and (deletion) and Dalalthma on the social meanings in part (28) of the Holy Quran (Journal of the College of Education for Women, 2019)
Arabic language , like any other living languages grow and evolve ; social phenomenonit is subject to the law of life ; therefore resemble organism also touted as the most eloquentlanguage and the ability to meet the needs of people in every time and place.The contemplation of the verses of the Koran reveals a lot of means of expressionleading to the grammatical meaning of the social.I have tried in this research that investigated the social meanings through the phenomenaof deletion and delivery delays and capture semantic landing through the meanings that leadto psychological persuasion to comply with the orders after the rights of the divine in whichsocial directives.It remains the greatest mystery of the miracles of the Quran in its ability to change tochange any human being , as well as the miracle that lies in his style , and his eloquence , andhis challenge to humanity that is valid for all times and places